Artemisinin kills malaria parasites by damaging proteins and inhibiting the proteasome - Jessica L. Bridgford (Nature Portfolio, 2018)
Artemisinin (ART) is a widely used antimalarial drug, but its mechanism of action is poorly understood. Here, Bridgford et al. show that ART kills parasites by a two-pronged mechanism, causing protein damage and compromising proteasome function, and that accumulation of proteasome substrates activates the ER stress response.